If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -86 = -2(1 + -6a) -86 = (1 * -2 + -6a * -2) -86 = (-2 + 12a) Solving -86 = -2 + 12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12a' to each side of the equation. -86 + -12a = -2 + 12a + -12a Combine like terms: 12a + -12a = 0 -86 + -12a = -2 + 0 -86 + -12a = -2 Add '86' to each side of the equation. -86 + 86 + -12a = -2 + 86 Combine like terms: -86 + 86 = 0 0 + -12a = -2 + 86 -12a = -2 + 86 Combine like terms: -2 + 86 = 84 -12a = 84 Divide each side by '-12'. a = -7 Simplifying a = -7
| 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 | | 4(2x-5)=43 | | -37=-3(1+6m)-2(m+7) | | 3m^3-15m^2+75m=0 | | x^2+y^2-22x+112=0 | | 2b-5b=-9 | | (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 | | 9-ln(4-x)=0 | | 4x=-5+2x+18 | | -2(-9w+1)-2w=2(w-1)-2 | | 2x+13=5x-14 | | 5y=2(y+6) | | -5w+3(w-5)=-13 | | 3*2-y=9 | | 3*3-y=9 | | 4x=8+3x | | 2b^4+8b^3+8b^2=0 | | 5+4D=47 | | 6(6v+5)=1+6v | | 7x+6=9x+x | | 250+.10y=350 | | x^2+y^2+30x-2y+210=0 | | 8.5X=11 | | x+.10y=350 | | 600+600= | | 5(x+5)=-5(2x-3)+x | | 23+6y-15=62 |